FAKTOR PENYEBAB TERJADINYA HIPERTENSI PADA IBU HAMIL - Maryana, Nana; Mustary, Musliha; Rotinsulu, Ria Angelina Jessica; Herniyatun, Herniyatun (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Hypertension is a medical condition in which a person's blood pressure shows systolic numbers ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg. Based on data obtained from the Pattallassang Health Center, the percentage of pregnant women suffering from hypertension has increased every year. In 2020, 12.5% of pregnant women were diagnosed with hypertension. This figure increased in 2021 to 20.85%, and in 2022 it was recorded that 23.15% of pregnant women suffered from hypertension. A significant increase continued in 2023, with 25.74% of pregnant women experiencing hypertension. The purpose of the study was to determine the factors that cause hypertension in pregnant women. The research design used in this study was corss sectional. The research was conducted in June 2023 at the Pattallassang Health Center. The population is all pregnant women with a total of 245 people at the Pattallassang Health Center, Takalar Regency for the period January-June 2023. The sample amounted to 152 respondents selected using simple random sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed there was a relationship between the age of pregnant women (p value: 0.000) and parity (p value: 0.037) on the incidence of hypertension in pregnant women. It is recommended that pregnant women should more regularly check or control blood pressure so that early signs of hypertension can be detected, especially for pregnant women who are <20 years old and >25 years old.Keywords: Hypertension, Pregnant Women, Parity.